2005
DOI: 10.1081/stm-200056037
|View full text |Cite
|
Sign up to set email alerts
|

A Tandem Queue with Server Slow-Down and Blocking

Abstract: C e n t r u m v o o r W i s k u n d e e n I n f o r m a t i c a PNA Probability, Networks and Algorithms Probability, Networks and AlgorithmsCWI's research has a theme-oriented structure and is grouped into four clusters. Listed below are the names of the clusters and in parentheses their acronyms. A tandem queue with server slow-down and blocking ABSTRACT We consider two variants of a two-station tandem network with blocking. In both variants the first server ceases to work when the queue length at the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Another minor problem is that the function V 2 (x) is not smooth around (α 2 , 0). Specifically for x 2 < δ/γ 2 , the gradient of V 2 (x) is not continuous around the vertical line (x 1 , ·) where the first component satisfies f (x 1 , δ/2γ) = 0 with f (x) as defined in (17). Without going into details, we propose to use any suitable mollification procedure to make V 2 (x) a smooth function, and from now on we will treat V 2 (x) as such.…”
Section: Asymptotically Efficient Scheme For µ 1 ≤ µmentioning
confidence: 99%
See 1 more Smart Citation
“…Another minor problem is that the function V 2 (x) is not smooth around (α 2 , 0). Specifically for x 2 < δ/γ 2 , the gradient of V 2 (x) is not continuous around the vertical line (x 1 , ·) where the first component satisfies f (x 1 , δ/2γ) = 0 with f (x) as defined in (17). Without going into details, we propose to use any suitable mollification procedure to make V 2 (x) a smooth function, and from now on we will treat V 2 (x) as such.…”
Section: Asymptotically Efficient Scheme For µ 1 ≤ µmentioning
confidence: 99%
“…[11]; this complication does not play a role when analyzing rare-event probabilities related to the total network population. We expect that the above-mentioned large-deviations heuristic can be rather helpful when analyzing a broad class of networks; see also earlier results in [13] for the model that was introduced in [17], in which the service rate of the first queue depends on the content of the second queue. The proof technique is essentially based on that of Dupuis et al [7], but, as in De Boer and Scheinhardt [4], we have managed to simplify the proofs considerably.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we study such a model: a tandem queue that consists of two nodes or servers, where, in order to protect the second (downstream) queue from overflow, the first (upstream) server keeps track of queue length at the second server, and lowers its service rate when the second queue is large. In [3] this model was already introduced and the consequences for the first queue were studied, but here our main interest is to determine the probability of overflow in the second queue during a busy cycle. Here we define a busy cycle as the time between two consecutive arrivals to an empty system.…”
Section: Introductionmentioning
confidence: 99%
“…Upon combining the fact that W 2 (x) ≥ W 1 (x) − δ for any x ∈D ∪D + (this is shown in the same manner as in Thm. 5.7 of [15]; use (20)), with the monotonicity of γ(x) in both x 1 and x 2 , and using definition (33), it is found that…”
Section: Lemma 45mentioning
confidence: 99%
“…For this model only partial results are available, see e.g. [20]. It is noted that the slow-down model is of significant practical interest, as a related mechanism has been proposed e.g.…”
Section: Introductionmentioning
confidence: 99%